(untitled) (Medico Legal Update, 2021)
The objective of this study was to estimate stature from nasal measurements in South Indian population. The study was done using standard measuring apparatus measuring tape and vernier calipers including both males and females. Regression formula and correlation was derived between nasal dimensions and stature. In this study, regression formula is derived with three variables generalized for both males and females, S= 118.005+6.804NL+4.003NW+0.254NH ? 9.70100. Linear Regression equation for males and females have been derived separately with each of the nasal parameters. In conclusion nasal measurements can be an effective tool in estimating stature.